The Hubungan Tingkat Sosial Ekonomi Keluarga Dengan Perilaku Picky Eater Pada Anak Usia 4-6 Tahun di Kecamatan Lowokwaru Kota Malang - Rahmah, Putri Nadia Khoirina; Samawi, Ahmad; Maningtya, Rosyi Damayani Twinsari (UNIB Press, 2025)
The purpose of this study was to determine whether there is a relationship between the socio-economic level of the family and picky feeding behavior in children, this is because there has been no research that discusses the relationship between the two variables so that this study will be a new science in the field of early childhood education. Picky feeding behavior in children is interpreted as picky eating behavior, only wanting to eat certain foods, and being reluctant to try new foods. The population obtained was the number of guardians at the school where the study was conducted, which was 247 people, with a research sample of 71 people obtained from the simple random sampling technique. Collecting respondent data using a questionnaire on picky feeding behavior and family socio-economic level. The results showed that in Lowokwaru District there were all socio-economic levels of families, but most of the people were in the middle to upper category. The results of 32 (45,1%) of 71 samples showing picky eating behavior, while 39 (54,9%) samples showed non-picky eating behavior. The statistical test conducted obtained a sig. = 0.000 (sig <0,005) which means that there is a relationship between the socio-economic level of the family and picky eater behavior in children in Lowokwaru District. This study shows that most children who have picky feeding behavior come from families with middle to upper socio-economic levels, thus forming a positive relationship because high socio-economic levels tend to influence an increase in picky feeding behavior. The relationship that occurs between these two variables is also classified as strong and has a contribution value of 42,5% obtained from the results of the linear regression test.